2012
DOI: 10.3892/ol.2012.848
|View full text |Cite
|
Sign up to set email alerts
|

Primary giant lymphoma of the right thigh: A case report and brief review of the literature

Abstract: Abstract. Primary soft tissue non-Hodgkin lymphoma (NHL) of the extremities is very rare. The clinical features of NHL mimic those of other soft tissue tumors, particularly sarcoma; however, they should be differentiated, as the treatment and prognosis are completely different. In this study, the case of a 68-year-old female with a giant mass, movement disorder, numbness and painful sensations in the right thigh is presented. Magnetic resonance (MR) imaging revealed a huge circle-shaped mass. Fine needle aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Extranodal involvement of NHL is approximately 20%‐30% . Primary extranodal, located only on the extranodal site, commonly arise from gastrointestinal tract whereas, primary skeletal muscle non‐Hodgkin's lymphoma (PSM NHL) is rare, and constitutes up to 0.1 to 0.5% of NHL . Skeletal muscle is involved by lymphoma either in the course of disseminated disease, spread from contiguous lymph node or as a primary extranodal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal involvement of NHL is approximately 20%‐30% . Primary extranodal, located only on the extranodal site, commonly arise from gastrointestinal tract whereas, primary skeletal muscle non‐Hodgkin's lymphoma (PSM NHL) is rare, and constitutes up to 0.1 to 0.5% of NHL . Skeletal muscle is involved by lymphoma either in the course of disseminated disease, spread from contiguous lymph node or as a primary extranodal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC is a highly accurate, safe and cost-effective method, which is widely used in initial tests for the histopathological evaluation of neck masses (1). However, it is not recommended for the diagnosis of malignant lymphoma because the tumor tissue architecture cannot be obtained (1,6). Based on the FNAC results of the present study, malignancy was found in only one case and atypical lymphoid lesions were suspected in three cases.…”
Section: Discussionmentioning
confidence: 62%
“…Accurate diagnosis and treatment of solitary large malignant lymphoma requires multidisciplinary collaboration (5,6). The histopathologic examination through surgical excision and subtype confirmation through immunophenotyping are essential (1)(2)(3)(4)(5)(6)(7). Treatment for malignant lymphoma of the head and neck may include systemic chemotherapy with or without radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations